Growth Response of Three Shallot Varieties (Allium Ascalonicum L.) From True Shallot Seed Given a Combination of Phosphorus and Potassium Fertilizer in Dry Land - Ika Medayanti; Kartina Kartina; Susiyanti Susiyanti; Zahratul Milla (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
The research was conducted at the Experimental Garden of the Integrated Agricultural System of the Banten Province Agricultural Service at an altitude of 60 m above sea level. from July to September 2021. The design of this study using a factorial randomized block design, the first factor varieties treatment consists of 3 levels: v1 = Maserati varieties, v2 = Sanren varieties, and v3 = Tuk Tuk varieties. Factor fertilization treatment consists of 3 levels: p1 = 54 kg/ha P2O5 + 90 kg/ha K2O, p2 = 72 kg/ha P2O5 + 120 kg/ha K2O, and p3 = 90 kg/ha P2O5 + 150 kg/ha K2O. The results showed that there was no interaction between varieties and combinations of P and K fertilizers on all observed parameters. Varieties treatment affected the number of leaves 5 weeks after planting, leaf area, plant wet weight and plant wet weight per plot, where the sanren variety had the best value, successively 16.5 strands; 499.28 cm2; 86.90 grams and 2105.01 g. The combination of fertilizer application of 90 kg/ha P2O5 + 150 kg/ha K2O was the best for the parameters of leaf area, wet weight per plant and wet weight per plot, respectively 482.02 cm2; 82.37 grams; and 2065.61 grams.